PROBLEMATIC SIDES IN IMPLEMENTING LEARNER-CENTERED INSTRUCTION PARADIGM IN ENGLISH CLASSROOM - Absharini Kardena (Fakultas Bahasa dan Seni UNP, 2014)
ASALAHAN DALAM PENERAPAN PARADIGMA LEARNER-CENTERED INSTRUCTION DALAM KELAS BAHASA INGGRIS AbstractThe implementation of Learner-Centered Instruction paradigm (LCI) is closely related to the role of teachers and students in the classroom. Roles that are run by teachers and students contribute to the successful of LCI implementation. In fact, LCI is still not going well, especially in MAN Solok. Indications suggest that the problems encountered in the implementation of the LCI are closely related to the way teachers and students in implementing their role. This article discusses the implementation of the respective roles of teachers and students in MAN Solok. In addition, this article also discusses the problems arised in the implementation of LCI and its causes.AbstrakPenerapan paradigma Learner-Centered Instruction (LCI) berkaitan erat dengan peran guru dan siswa dalam kelas. Peran yang dijalankan oleh guru dan siswa berkontribusi terhadap keberhasilan pelaksanaan LCI. Pada kenyataannya, LCI masih belum berjalan dengan baik, khususnya di MAN Kota Solok. Indikasi-indikasi yang ada menunjukkan bahwa masalah yang dihadapi dalam pelaksanaan LCI berkaitan erat dengan cara guru serta siswa dalam menjalankan peran mereka masing-masing. Artikel ini membahas pelaksanaan peran masing-masing guru dan siswa di MAN Kota Solok. Selain itu, artikel ini juga membahas masalah yang muncul dalam pelaksanaan LCI beserta penyebab-penyebabnya.Kata Kunci: implementasi, learner-centered instruction,paradigma, kelas bahasa Inggris